Care for ill-housed persons: access and professional proactivity in primary care - Lucas Alves Gontijo; Bruna Moreira da Silva; Marcelo Pedra Martins Machado; Daniela Priscila Oliveira do Vale Tafner; Edilene Aparecida Araújo da Silveira; Valéria Conceição de Oliveira; Eliete Albano de Azevedo Guimarães; Selma Maria da Fonseca Viegas (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to understand access to primary care for ill-housed persons and professional proactivity in municipalities without a Street Outreach Office. Method: a qualitative approach study, under the Grounded Theory methodological framework and Symbolic Interactionism theoretical framework, carried out with 30 Family Health Strategy professionals and six key informants from the Socio-Assistance Network, using open-ended interviews and memos. Results: the lack of planning for health care for ill-housed persons was evident. Access occurs through spontaneous demand and, almost always, under the intervention of Social Assistance Network professionals. Intersectoral and proactive professional work were highlighted as axes in overcoming inequities and guaranteeing access. Final considerations: the need to expand access is ratified, with identification, registration and monitoring of ill-housed persons in primary care. It is necessary to encourage professional proactivity, given their notoriety in strengthening equitable actions.